Volunteer Capability Development in Community Empowerment Activities of Indonesian Youth - Putri, Karina Isnaini; Prihatin, Silverius Djuni (MUHARRIK: Jurnal Dakwah dan Sosial, 2023)
Yayasan Arah Pemuda Indonesia organised a community empowerment activity with the theme pengabdi muda #5. Pengabdi Muda #5 has a series of activities that serve to optimise the capabilities of volunteers so that they have provisions in carrying out community empowerment. This research uses the learning outcomes capability theory from Robert Mills Gagne and the 7 stages of proposition proposed by Isbandi Rukminto Adi. The theory will dissect the process of developing volunteer capabilities at Arah Pemuda Indonesia Foundation. This research uses a descriptive qualitative approach. Data collection techniques include observation, documentation, and interviews. This study found that the series of community empowerment activities of youth service #5 can optimise volunteer capabilities. The implementation stage is the most important stage that can develop volunteer capabilities. Pengabdi Muda #5 activities are still limited in carrying out community empowerment because the stages of empowerment and capacity building are not optimal, but the awareness stage has been carried out and is a very good agent of change.